1984
DOI: 10.1007/bf00583874
|View full text |Cite
|
Sign up to set email alerts
|

Transport ofl-cystine in isolated perfused proximal straight tubules

Abstract: Unidirectional fluxes of L-35S-cystine and intracellular 35S activity were measured in isolated perfused segments of rabbit proximal straight tubule. The absorptive (lumen-to-both) flux of L-35S-cysteine showed a tendency toward saturation within the concentration limits imposed by the low solubility of cystine (0.3 mmol . l-1). In contrast, for the bath-to-lumen fluxes, there was a linear relation between the bathing solution concentration of L-35S-cystine and the rate of 35S appearance in the lumen. Nonlinea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
14
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 32 publications
3
14
0
Order By: Relevance
“…After hybridiza- [Cystine] (gM) previously demonstrated by in situ hybridization that D2 from rat is expressed specifically in the proximal tubule S3 segment of the rat kidney outer medulla, a region of high affinity brush border amino acid transport ( 18). This localization is consistent with in vitro microperfusion studies of proximal tubule segments using rabbit ( 19) and rat kidney (20) 150-400-fold, the function of these proteins is not clearly understood. We have suggested that D2 may represent a transport regulator or regulatory subunit of a heterodimeric transporter (1,3,5).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…After hybridiza- [Cystine] (gM) previously demonstrated by in situ hybridization that D2 from rat is expressed specifically in the proximal tubule S3 segment of the rat kidney outer medulla, a region of high affinity brush border amino acid transport ( 18). This localization is consistent with in vitro microperfusion studies of proximal tubule segments using rabbit ( 19) and rat kidney (20) 150-400-fold, the function of these proteins is not clearly understood. We have suggested that D2 may represent a transport regulator or regulatory subunit of a heterodimeric transporter (1,3,5).…”
Section: Resultssupporting
confidence: 84%
“…The potential role of the D2 protein in human inherited diseases ofamino acid transport, such as cystinuria and Hartnup disorder, is intriguing. D2 and D2H exhibit Km values for cystine and dibasic amino acids, and tissue specific expression similar to those previously described for the transporter predicted to be defective in cystinuria (6,19,21 ). Ifthe potential compensation for neutral amino acid uptake from multiple other amino acid transporters (e.g., system L) is taken into account, then a defect in the D2 protein could explain the impaired cystine and dibasic amino acid excretion seen in cystinuria (22).…”
Section: Resultssupporting
confidence: 70%
“…49). After functional characterization of rBAT (2,46,56), the demonstration that it is the type I cystinuria gene (5,40), and its main localization to the S3 segment of the proximal tubule (18) (where the low-K m system had been functionally localized) (46), it appeared that rBAT, together with an unidentified light subunit, constituted this low-K m system (1,13) [note that the S3 expression of rBAT did not fit with cystine reabsorption (see below)]. Although b 0,ϩ AT was later shown to be the non-type I cystinuria gene (14), and it induced the low-K m system on coexpression with rBAT in cell lines and oocytes (7,14,35), the low expression overlap with rBAT obscured the role of each protein in cystine transport in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…This high affinity system is shared with dibasic amino acids and shows heteroexchange diffusion of dibasic amino acids and cystine (17-19, 42). Transport of L-cystine, examined at low ( M) concentration, is inhibited by some L-neutral amino acids, suggesting a high affinity cystine transporter shared with neutral amino acids (18,(22)(23)(24). The sodium dependence of cystine reabsorption has been controversial for years; the high affinity cystine uptake in rat brush border membranes was first believed to be sodium-dependent and, later, sodium-independent (18,43).…”
Section: Discussionmentioning
confidence: 99%
“…This transport was shown to be defective in biopsies of intestinal mucosa from cystinuric patients (20 -22). The sodium dependence of this reabsorption system is controversial, as is its interaction with neutral amino acids, since no hyperexcretion of neutral amino acids occurs in cystinuria (17)(18)(19)(22)(23)(24). Second, the role of rBAT in the b 0,ϩ -like transport mechanism is unknown.…”
mentioning
confidence: 99%